On the role of sidewalls in the transition from straight to sinuous bedforms - Zgheib, N. (2019)
We present results from direct numerical simulation on the transition from straight‐crested to sinuous‐crested bedforms. The numerical setup is representative of turbulent open channel flow over an erodible sediment bed at a shear Reynolds number of Reτ = 180. The immersed boundary method accounts for the presence of the bed. The simulations are two‐way coupled such that the turbulent flow can erode and modify the bed, and in turn, the bed modifies the overlying flow. Coupling from the flow to the bed occurs through the Exner equation, while back coupling from the bed to the flow is achieved by imposing the no‐slip and no‐penetration condition at the immersed boundary.